The Field Confinement, Narrow Transmission Resonances, and Green Function of a Multilayered Microsphere with Metamaterial Defects. (24th October 2011) - Burlak, Gennadiy; Díaz-de-Anda, A.
Abstract : We numerically investigate the optical transmission through a compound spherical stack with conventional and metamaterial (MM) layers and also embedded MM defect. A formation of extremely narrow resonant peak with nearly complete transmittance in area of a band gap is found. We demonstrate that photon fields of certain frequencies can be strongly confined by a left-handed (LH) defect. The influence of a random deviation in the width of compound spherical layers as well the transit to the whispering gallery mode (WGM) is also discussed.